2014
DOI: 10.1371/journal.pone.0105808
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Storage Temperature on Cultured Epidermal Cell Sheets Stored in Xenobiotic-Free Medium

Abstract: Cultured epidermal cell sheets (CECS) are used in regenerative medicine in patients with burns, and have potential to treat limbal stem cell deficiency (LSCD), as demonstrated in animal models. Despite widespread use, short-term storage options for CECS are limited. Advantages of storage include: flexibility in scheduling surgery, reserve sheets for repeat operations, more opportunity for quality control, and improved transportation to allow wider distribution. Studies on storage of CECS have thus far focused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 48 publications
4
24
1
Order By: Relevance
“…The slight differences between the two methods might be explained by the more qualitative estimate of trypan blue exclusion versus quantification of fluorescent signal emitted by CAM. Viability was improved compared to results in our two-week storage study 17 where cell viability values in temperature groups between 4 °C and 37 °C typically ranged between ~20% and ~60%. Cell viability was comparable at 24 °C between the two studies (~90% normalized to control).…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…The slight differences between the two methods might be explained by the more qualitative estimate of trypan blue exclusion versus quantification of fluorescent signal emitted by CAM. Viability was improved compared to results in our two-week storage study 17 where cell viability values in temperature groups between 4 °C and 37 °C typically ranged between ~20% and ~60%. Cell viability was comparable at 24 °C between the two studies (~90% normalized to control).…”
Section: Discussioncontrasting
confidence: 51%
“…We have previously shown that temperature has a significant impact on the quality of stored cultured cells from a variety of tissues 13 16 . Based on analyses of phenotype (best at 12 °C) and viability (best at 24 °C) of CES in our two-week storage study 17 , 18 , we hypothesized that 12 °C may be most promising for retention of proliferative capacity and undifferentiated cell phenotype in CES following one-week of storage. Therefore, in-depth analyses were carried out herein to compare one-week storage of CES stored at temperatures 4 °C, 8 °C, 12 °C, 16 °C, and 24 °C with non-stored control cell sheets.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the challenges that are inherent to cryopreservation, our goal was to develop an easily implementable and inexpensive short-term storage method for cultured HOK. Previous publications on storage of cultured epithelial cells [ 16 21 ] demonstrated that storage temperature profoundly affects the viability, phenotype, metabolism and morphology of these cells. We hypothesized that storage temperature will similarly affect cultured HOK and conducted the present study to define the optimal temperature for storage of HOK.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of serum poses a discrepancy in the context of broblast and keratinocyte co-culture. The presence of serum is required to support the proliferation of broblasts, which is in contrast to keratinocytes, which grow poorly or fail to attach and grow in the presence of serum, and are therefore cultivated in serum-free media (16,(25)(26)(27)(28). To overcome this, a large number of protocols for contact-based co-culture of broblasts and keratinocytes, start with growing con uent layers of broblasts in media supplemented with high concentrations of animal serum (up to 10%), after which keratinocytes are seeded on broblast layers in serum-free media (10,11,15,16,19).…”
Section: Introductionmentioning
confidence: 99%